Implementation of Solutions-Focused Counseling (SFC) to Improve Student Motivation: A Single Subject Research - Lintang Setiono; Marjohan Marjohan; Marlina Marlina (Department of Special Education, 2019)
This research aims to examine the effectiveness of solution-focused counseling to improve student learning motivation. The research is conducted using Single Subject Research design. The research subjects were five eight-grade students who have very low learning motivation. The instruments for data collection are learning motivation scale, interview, and observation. The data were analyzed using descriptive analysis. The findings indicated that the counseling effectively improves student learning motivation. Based on the research findings, it is suggested that counselors apply SFC in counseling both in individuals and in groups.